Determination of cobalt, iron, and nickel in high-purity silicon by high-resolution continuum source graphite furnace atomic absorption spectrometry employing solid sample analysis - Bechlin, Marcos André [UNESP]; Barros, Ariane Isis [UNESP]; Babos, Diego Victor [UNESP]; Ferreira, Edilene Cristina [UNESP]; Neto, Jose Anchieta Gomes [UNESP] (My University, 2017)
This paper describes the development of analytical methods for the determination of cobalt, iron, and nickel in pure silicon for photovoltaic and electronics applications based on solid sampling (SS) coupled to a high-resolution continuum source graphite furnace atomic absorption spectrometer (HR-CS GFAAS). Samples were also analyzed by line-source flame atomic absorption spectrometry (LS FAAS) as a comparative technique after acid microwave-Assisted digestion. Cobalt, Fe, and Ni were determined in samples of solar- grade silicon (SoG-Si) and elec-Tronic-grade silicon (EG-Si) by SS HR-CS GFAAS and LS FAAS. A paired f-Test at a 95% confidence level showed that the SS HR-CS GFAAS methods achieve similar results to those obtained by LS FAAS. The relative standard deviations (n= 12) for a sample containing 7.80 mg kg-1 Co, 36.2 mg kg-1 Fe, and 228.5 mg kg1 Ni were 6.4% for Co, 6.1% for Fe, and 1.0% for Ni for SS HR-CS GFAAS. For the SS HR-CS GFAAS, the limits of detection were 0.39 mg kg1 Co, 1.14 mg kg1 Fe, and 5.71 mg kg1 Ni. Accuracy was also checked by the analysis of high- purity silica spiked with Co, Fe, and Ni, and the recoveries were at 94.3-97.1% (Co), 86.7-109% (Fe), and 88.4-98.9% (Ni).